A COMPARATIVE STUDY ON THE DUTIES OF THE AUTHORITIES HANDLING THE VIOLATION AND BREACH OF LAW BY THE ADMINISTRATIVE UNITS IN IRAN AND FRANCE - Mohammad Mazhari, Fatemeh Jangjooy Khelejan, Farzaneh Monadi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Forming a democratic society requires paying attention to people rights. Since in an unequal administrative laws, the relationships between the government and individuals are built on the basis of power, the government can always make one-sided decisions and enforces them using public power, in return people have the right to object to anti-law and out-of-jurisdiction decisions and measures of the officials. So, the existence of a reference which handles complaints from the executive administrations is essential. In Iran, this duty is on the Court of Administrative Justice and in France it is on the Governmental Council. In comparison with the Governmental Council, the jurisdiction of the Court of Administrative Justice encompasses a limited domain of government organizations. In addition, the lack of a precise criterion to identify the entity of the issues that can be raised in the Court of Administrative Justice has brought up some problems to judicial supervision. However, the Governmental Council has divided its judicial supervision with other administrative courts and has accepted wide variety of cases and in general the bases of the cases are interpreted wider in the Governmental Council. In this paper, in addition to clarifying the duties and jurisdiction of these administrative references, their structures and basic differences have been discussed.